Research on quantitative evaluation of medical insurance fraud supervision policy based on ‘Antecedents-Process-Outcomes’ framework - Zixiao Zhang; Shaoqun Ding; Zitao Yang; Huaxia Hu (PLoS ONE, 2025)
Fraud in medical insurance is a serious problem that threatens the safety and sustainability of medical insurance funds. The process of reducing or even eliminating the impact of fraud is related to maintaining the balance of payments for medical insurance funds and reforming the payment system based on total amount control. As a result of reviewing the policy background of medical insurance fraud in China, combined with the policy evaluation model in the area of public management, this paper develops a conceptual framework of ’Antecedents-Process-Outcomes’ that emphasizes the fraud and governance of medical insurance funds. This paper uses grounded theory to look at 180 cases of medical insurance fraud and then uses the PMC index model to rate 18 policies. It then looks at the joint progressive analysis framework of medical insurance fraud and fraud supervision. In this paper, we analyze the policy similarities and differences of medical insurance fraud supervision in China from three perspectives: policy attributes, policy contents, and policy effects. The average PMC index of the 18 policies is 4.98, which is generally acceptable; however, there are some deficiencies in the policy field, policy supervision chain, policy orientation, and policy tools. Then, it puts forward suggestions for improving the four policy shortcomings in order to provide theoretical and practical enlightenment for the high-quality development of the medical security system and realize the new medical security in the process of Chinese-style modernization.